2019
DOI: 10.1089/wound.2018.0856
|View full text |Cite
|
Sign up to set email alerts
|

Fibroin and Polyvinyl Alcohol Hydrogel Wound Dressing Containing Silk Sericin Prepared Using High-Pressure Carbon Dioxide

Abstract: Objective: To fabricate and investigate the properties of fibroin and polyvinyl alcohol (PVA) hydrogels containing sericin prepared using high-pressure carbon dioxide (CO 2). Approach: In this study, fibroin/PVA hydrogels with and without sericin were prepared using the high-pressure CO 2 method. The physical and mechanical properties of the hydrogels were investigated using field-emission scanning electron microscopy, Fourier-transform infrared spectroscopy, thermogravimetric analysis, and differential scanni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 39 publications
0
10
0
Order By: Relevance
“…Hydrogels are polymers with a three-dimensional network structure formed by covalent bonds, hydrogen bonds, van der Waals force, or ionic bonds. [1][2][3][4][5][6][7] With the advantages of adhesion, biocompatibility, and degradability, hydrogels are biomaterials with excellent performance and have important applications in tissue engineering, [8][9][10] wound dressing, [11][12][13][14] drug delivery, [15][16][17][18][19] and so on. Hydrogels can be divided into intelligent hydrogels and non-intelligent hydrogels.…”
Section: Introductionmentioning
confidence: 99%
“…Hydrogels are polymers with a three-dimensional network structure formed by covalent bonds, hydrogen bonds, van der Waals force, or ionic bonds. [1][2][3][4][5][6][7] With the advantages of adhesion, biocompatibility, and degradability, hydrogels are biomaterials with excellent performance and have important applications in tissue engineering, [8][9][10] wound dressing, [11][12][13][14] drug delivery, [15][16][17][18][19] and so on. Hydrogels can be divided into intelligent hydrogels and non-intelligent hydrogels.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have used CO 2 to facilitate or trigger hydrogel fabrication based on pH changes, expecting that the CO 2 would be released from the hydrogel into the atmosphere. Some studies have reported that the formation of LM pectin/CaCO 3 hydrogels and alginate/CaCO 3 hydrogels can be stimulated by employing high-pressure or supercritical CO 2 to dissolve a considerable amount of CO 2 in polymer-containing gelation mixtures. In these methods, the temperature and pressure of CO 2 are essential parameters to control the physicochemical properties of the final hydrogels.…”
Section: Introductionmentioning
confidence: 99%
“…The silk proteins sericin and fibroin, which are obtained from Bombyx mori cocoons, are significant sources of natural biopolymers [6]. Silk protein was once thought to be a waste product from the silk industry, produced during the grafting process after the cocoon had been boiled.…”
Section: Introductionmentioning
confidence: 99%
“…When the silk protein cocoon is heated, the silk protein is washed off and discarded. However, numerous studies have shown that silk proteins have a wide range of beneficial properties, including the ability to be used as a medicine, dietary supplement, or ingredient in cosmetic products [6][7][8]. It also has anti-tyrosinase, which has antioxidative, anti-inflammatory, and moisturizing properties [6,9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation